2004
DOI: 10.1093/bioinformatics/bth230
|View full text |Cite
|
Sign up to set email alerts
|

BioMercator: integrating genetic maps and QTL towards discovery of candidate genes

Abstract: Available upon request (http://moulon/~bioinfo/BioMercator/). Free of charge for academic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
337
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(345 citation statements)
references
References 6 publications
0
337
0
Order By: Relevance
“…In systems where more QTL studies have been conducted, more formal meta-analyses and computation of a composite map combining several densely genotyped panels may further improve the confidence of QTL/candidate gene colocalization and thus also improve the efficiency of this approach (Arcade et al 2004;Chardon et al 2004). Several observations suggest that genetic hitchhiking is a concern that impacts how effectively improvement loci can be identified, however.…”
Section: Discussionmentioning
confidence: 99%
“…In systems where more QTL studies have been conducted, more formal meta-analyses and computation of a composite map combining several densely genotyped panels may further improve the confidence of QTL/candidate gene colocalization and thus also improve the efficiency of this approach (Arcade et al 2004;Chardon et al 2004). Several observations suggest that genetic hitchhiking is a concern that impacts how effectively improvement loci can be identified, however.…”
Section: Discussionmentioning
confidence: 99%
“…The Haldane mapping function was used to convert recombination frequencies into map distances (Haldane 1919). The chart of the linkage map was generated using BioMERCATOR v.3.1 (Arcade et al 2004). QTL analysis QTL analyses using the SSR-SNP linkage map and all available genotypic and phenotypic data were performed with the MapQTLÂź5 software (Van Ooijen 2004).…”
Section: Linkage Mappingmentioning
confidence: 99%
“…For the hybrid parent SA65T, the species origin of the QTL marker alleles were identified, and the allelic effects at the QTL were therefore estimated by contrast of E. oleifera (grandparent SA49D) against E. guineensis (grandparent LM2466P). The QTLs (position, confidence interval, variation explained) were visualized on the linkage map using BioMERCATOR v.3.1 (Arcade et al 2004).…”
Section: Linkage Mappingmentioning
confidence: 99%
“…This statistical approach enables QTL results from independent studies to be combined into a single result using only published QTL data. Software packages based on this methodology are available such as BioMercator (Arcade et al 2004) and Meta-QTL (Veyrieras et al 2007), a new software that removes some of the limitations of BioMercator in the number of QTLs it can handle at once. Meta-QTL analyses for flowering time in maize ), resistance to a nematode in soybean (Guo et al 2006), earliness in bread wheat (Hanocq et al 2007), and N uptake in maize (Coque et al 2008) have already shown the usefulness of this approach in determining the number of "true" QTLs underlying the observed QTLs and in positioning consensus QTLs with more precision.…”
Section: Introductionmentioning
confidence: 99%